Prevalence study of gastrointestinal parasites in psittacine birds in the Klang Valley - Lee, Natasha Yu Pheng; Abu, Jalila; Babjee, Shaik Mohamed Amin; Lee, Chu Chong; Moktar, Maizatul Akmal (2005)
A total of 132 faecal samples of psittacine birds were collected from 11 pet shops, a zoo, a bird park and two individual bird owners from around the Klang Valley, Malaysia. From these samples, 53 were obtained from individually kept birds and 79 from birds kept in a group. The birds were classified into 15 groups: African Grey Parrots, Amazon Parrots, Budgerigar, Cockatiel, Cockatoos, Conures, Eclectus Parrots, Hanging Parrots, Lories/Lorikeets, Lovebirds, Macaws, Parakeets, Poicephalus, Rosellas, and a mixed psittacine. Each faecal sample was examined by direct smear, formal-ether sedimentation and modified acid fast staining. The results revealed the presence of amoeba (3.8%), ascarid (1.5%), Capillaria (0.8%), Eimeria (6.1%), trematode (0.8%), Giardia (3.0%), and Strongyloides (3.8%). Birds kept in groups were found to have a significantly higher percentage of parasites (21.5%) compared to birds kept individually (7.5%). The number of positive samples examined by direct smears and formal-ether sedimentations did not differ significantly. The modified acid fast staining technique revealed Giardia instead of Cryptosporidium. This study is the first in Malaysia and may help in the differential diagnosis when gastrointestinal parasitism is highly suspected